Assessing the Evidentiary Value and Admissibility of Electronic Records in the Digital Age: An In-Depth Analysis: Examining the Challenges and Implications of Electronic Records in Legal Proceedings (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Electronic Evidence has become a mainstay of correspondence, management, and recordingbecause to the enormous advancement in e-administration in both the public and private sectors. Thesemany forms of electronic evidence are increasingly being used in civil and criminal litigation. Judges areregularly asked to monitor the acceptability of electronic confirmation during trials, and this has asubstantial impact on the outcome of the case, including whether the accused is found guilty orvindicated. The Court continues to struggle with this new electronic wilderness because theextraordinary concept of reconfirm, along with how easily it can be produced or falsified, creates abarrier to acceptance that cannot be addressed by alternative confirmations. The various types ofelectronic confirmation, such as site information, email, SMSMMS, interpersonal organisation contact,and PC-created reports, pose unique problems and challenges for legitimate verification and are subjectto a distinct arrangement of viewpoints.The Information Technology Act of 2000's Section 92 has modified the Indian Evidence Act (Beforerevision). The phrase All archives given for the evaluation of the Court has been changed in Area 3 ofthe Act to All reports, including electronic records prepared for the investigation of the Court. Theterms Substance of archives or electronic records have been substituted for Substance of reportswith regard to narrative confirmation, and Sections 65A and 65B have been incorporated to solidify theapplicability of electronic proof.